DAMPAK CONTRACT CHANGE ORDER PADA PEMBANGUNAN PROYEK GEDUNG TERINTEGRITAS RUMAH SAKIT JIWA MENUR SURABAYA - Kholili, Idham (Universitas Negeri Surabaya, 2023)
In the development process there is often a discrepancy between planning and actual conditions in the field. This will later be carried out by a change order contract as a material for submitting design changes, changes in structural calculations, to the addition and reduction of work items that cause changes in construction costs. Therefore, it is necessary to know the relationship between change order contracts and construction costs. This study uses data processing methods using the Statistical Package for Social Science (SPSS) program. The processed data was obtained from distributing questionnaires to all project managers in the Menur Mental Hospital Surabaya Integrity Building construction project. The results of the impact of the change order contract on construction costs led to additional overtime costs for workers with a correlation value of 0.826. Contract change orders have an effect on changes in construction costs in the Menur Mental Hospital Surabaya Integrity Building construction project, and for a variable that is very influential on changes in costs is the addition of workers' overtime costs.